BASED ON THE NUMERICAL SIMULATION OF COLD ROLL-BEATING FORMING RESIDUAL STRESS RESEARCH - CUI LiMu; XIAO JiMing (Jixie qiangdu)
When the load to be lifted after cold roll-beating forming the residual stress will appear, in order to effectively control its impact on the forming precision, now the relationship between roll-beating depth and the residual stresses were studied. According to basic principle of cold roll-beating, a finite element dynamic simulation model is established by ABAQUS software, the distribution of Mises force on the workpiece surface was obtained by dynamic simulation at different roll-beating depth. Because inner force of workpiece in result of dynamic simulation is at unbalance state, it cannot directly solve the residual stress, so the static simulation model is established on result of dynamic simulation, and the roll-beating depth of different roll-beating of forming gullet section residual stress in tangential direction, axial direction and radial direction is determined by static analysis. Experiment on self-developed cold roll-beating equipment, build experimental platform for residual stress measurement, and study on residual stress of cold roll-beating. The distribution of the tangential residual stress along the depth direction is obtained by the measurement of the workpiece under different roll-beating depth, the comparison between the experimental results and the finite element simulation results shows that the residual stress variation has a good consistency, which verified effectiveness correctly of the simulation model.